A comparative study of operative dynamic compression plating versus non-operative management in fracture shaft of humerus - Gaur, Naren; Singh, Naveen Kumar (International Journal of Research in Orthopaedics, 2020)
Background: Fracture shaft of humerus is among injuries which is commonly seen in clinical practice and frequently seen in polytrauma. Humerus shaft fractures account for 3% of all orthopedic injuries. Nonoperative treatment had been the mainstay of treatment for fracture shaft of humerus earlier. The association of conservative treatment with some morbidity, complications and prolonged immobilization leads to increase in various operative modalities of management. One of the commonly used operative modality is dynamic compression plating (DCP). In view of above considerations, a study was undertaken at our hospital which aimed to compare non-operative treatment with operative DCP for the management of fracture shaft of humerus. Aims and objectives of this study to compare the results of non-operative versus operative treatment of humerus shaft fracture. Methods: It was a prospective comparative study. Total 40 patients were taken for this study. 20 patients for operative and 20 patients for non-operative. Functional outcome was measured by the DASH scoring. P<0.05 was considered statistically significant. Results: Among the 40 patients 14 had excellent results, 12 had good, 8 had fair and 6 had poor results. Functional outcome scores were better for operative group as compared to non- operative group with p<0.0001. Conclusions: Dynamic compression plating of humerus is better method than conservative method because it achieves higher union rates.